The Effect of Compensation and Work Environment on Employee Work Motivation during the Covid 19 Pandemic at PT. Asoka Arians Properti - Medan - Fajar Rezeki Ananda Lubis (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of compensation and work environment on employee work motivation during the Covid-19 pandemic. This research was conducted at PT. Asoka Arians Properti - Medan which is located at Taman Asoka Asri Complex Jalan Plamboyan Medan was conducted in March 2021. The samples taken in this study were employees of PT. Asoka Arians Property - Medan. Determination of the number of samples in this study using the Slovin formula with a total sample of 31 respondents. Data analysis using multiple linear regression test. The results showed that simultaneously and partially compensation and the work environment had a significant effect on employee work motivation during the Covid-19 pandemic.